Exploring the Variation in First Year Undergraduates' Induction into Their Academic Disciplines - Min Yang (International Journal for the Scholarship of Teaching and Learning, 2011)
This study explored qualitative variation in first year undergraduates’ induction into the discipline in four dimensions: (1) induction into disciplinary knowledge, (2) induction into disciplinary research, (3) integration of learning from different courses, and (4) induction into disciplinary skills. Data were drawn from focus groups with students from different disciplines at a university in Hong Kong. Phenomenographic analysis identified four categories about induction into disciplinary knowledge and disciplinary research, and three categories regarding integration of learning. The categories were described in terms of the referential (aspects of the dimension discerned by students) and structural components (how students explained the aspects). A comparison of the categories revealed a hierarchical relationship among them. Content analysis showed cognitive skills, professional skills and study skills to be the important disciplinary skills for the students. Students’ varying conceptions of problem-solving and critical thinking skills implied qualitative differences in understanding about the nature of disciplinary problems.